The Relationship Between Parenting Style and Depression Levels in Early Adolescents - Lintang Putri Pramudita; Estin Yuliastuti; Suyatno Suyatno (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Depression among early adolescents can affect social, academic, and psychological development. Parenting style is one family-related factor associated with adolescent depressive symptoms. This study focused on early adolescents at SMP Negeri 3 Satu Atap Sumberlawang. Objective: This study aimed to examine the relationship between parenting style and depression levels among early adolescents. Methods: This quantitative cross-sectional study was conducted among students aged 12–14 years at SMP Negeri 3 Satu Atap Sumberlawang. A total of 146 students were included using a total sampling technique. Eligible participants were students in grades VII, VIII, and IX who provided assent and had parental/guardian consent; students who refused participation or were older than 14 years were excluded. Parenting style was assessed using the Parental Authority Questionnaire (PAQ), and depression levels were assessed using the Patient Health Questionnaire-9 (PHQ-9). PHQ-9 total scores range from 0 to 27 and were categorized as not depressed/minimal, mild, moderate, moderately severe, and severe depression. Data were analyzed using the Chi-square test. Results: Most respondents had a democratic parenting style (75/146; 51.4%). The largest depression category was not depressed/minimal (41/146; 28.1%). Parenting style was significantly associated with depression levels, χ²(8) = 49.80, p < 0.001, Cramer’s V = 0.413, indicating a moderate association. Conclusion: Democratic parenting style was associated with lower depression levels, whereas authoritarian and permissive parenting styles were associated with higher depression levels. Because this study used a cross-sectional design, the findings indicate an association and do not establish causality. Parents and schools should support adolescent mental health through appropriate communication, supervision, and emotional support.